A TRANSITIVITY ANALYSIS OF THE INDONESIAN PROTEST IN INTERNATIONAL ONLINE NEWS - Daniel Fernando Siahaan; Fabian Putra Nazreensyah; Hafwen Anargya; Rafi Muhammad Lubis; Rahmadsyah Rangkuti (Universitas Muhammadiyah Tapanuli Selatan, 2025)
In August 2025, Indonesia witnessed widespread protests across major cities as public anger grew over worsening economic conditions and controversial benefits granted to lawmakers. The demonstrations, initially sparked by a new Rp50 million (US3,000) monthly housing allowance for members of parliament, quickly developed into broader demands for transparency, fair governance, and accountability. Following the death of a civilian, Affan Kurniawan, during a police operation, the protests intensified and drew significant international media attention, making them a compelling case for examining how global news outlets represent political unrest. This study analyzes how four major international media organizations CNN, The Guardian, Al Jazeera, and Euro News portrayed these events using Halliday’s Transitivity System within the framework of Systemic Functional Linguistics (SFL). A total of 489 processes were identified and classified into Material, Verbal, Relational, Mental, and Behavioral types. The findings show that Material processes dominate across all articles, emphasizing physical actions and observable events. However, differences in word choice reflect each outlet’s distinct style: CNN stresses conflict and immediacy, The Guardian focuses on institutional context, Al Jazeera highlights emotion and human experience, and Euro News maintains factual neutrality. These results illustrate that linguistic selection not only reports events but also constructs ideological perspectives within global media discourse.